Unraveling the Oppressed Psyche: A Psychoanalytic Exploration of Female Oppression in The Yellow Wallpaper (1892) by Charlotte Perkins Gilman. - Tekouk, Afaf (My University, 2023)
In the depths of Charlotte Perkins Gilman's mesmerizing short story, The Yellow Wallpaper, lies a profound exploration of the female psyche and the complex interplay between psychological struggles and societal constraints. This present research work attempts to embark on a transformative journey, exploring together the narrative of the story by relying on Segmund Freud psychoanalysis concepts of the unconscious mind and repression. Through these lenses the study aims at unearthing the hidden truths that lie beneath the protagonist's crumbling sanity. With each turn of the page, we witness the protagonist's defiant rebellion against the suffocating norms that confine her and drive her to madness, defying expectations and challenging the very essence of societal constructs. This research stands as a testament to the enduring power of Gilman's words, inviting us to contemplate the intricate dance between the conscious and unconscious, and inspiring us to confront the complexities of the female psyche.
Keywords: Madness; female psyche; psychoanalysis; unconscious; wallpaper; repression